Economic and financial crisis based on Troika’s intervention and potentially avoidable hospitalizations - Loureiro da Silva, Cristina (2021)
Funding Information: The present publication was funded by Fundação Ciênciae Tecnologia, IP national support through CHRC (UIDP/04923/2020) and NOVA National School of Public Health. Publisher Copyright: © 2021, The Author(s). Copyright: Copyright 2021 Elsevier B.V., All rights reserved.